Religious Fanaticism and "Boko Haram" Insurgency in Nigeria: Implications for National Security - Austin O. Omomia (Centre for Behaviour and Wellness Advocacy, 2015)
Nigeria is commonly adjudged as the "Giant of Africa". No doubt, the African continent has witnessed drastic socio-political transformation between the periods 1960 to date. Ironically, since Nigeria became an independent nation on October, 1st 1960, she has been confronted with myriad of socio-political challenges. Notable among these, is religious fanaticism. This, in recent times, is encapsulated in grave religious insurgency, manifested in the "Boko Haram" challenge. This paper therefore addresses the relationship between religious fanaticism and security, how they affect each other (positively or negatively). It also examined the present security challenge in Nigeria, and attempts to advance some panaceas in achieving true security. Thus, articulating the benefits of security as genuine precursors for sustainable development of Nigeria. The paper applied historical and sociological methodology in its investigation. It is recommended among others, that the adherents of the different religions should embrace dialogue and tolerance. The government should also pursue the challenge posed by youth unemployment with the right vigour.